Building Morality and Ethics Through Islamic Religious Education In Schools - Bucky Wibawa Karya Guna; Sri Endah Yuwantiningrum; Firmansyah; Muh. Dzihab Aminudin S; Aslan (IJGIE (International Journal of Graduate of Islamic Education), 2024)
This comprehensive literature review explores the multifaceted dimensions of optimizing morality and ethics through Islamic religious education in schools. Delving into the growing field of Islamic education that can spur a new way of human life, from the beginning of life to its end are interrelated, this review synthesizes existing research, identifies trends, and offers insights for educators, policy makers, and researchers . The reason behind this exploration lies in the urgency to find out the level of morality of Islamic religious education in schools, namely: replacing the role of humans by automating a task or process. Strengthening the human role, namely presenting information, tasks, or processes. Restructuring or making changes to a task or process. This review covers various aspects, starting from Islamic religious education in schools, morality and ethics in Islam, Islamic religious education as a means of building morality, and the factors that influence it. By examining the interaction between aspects of morality and ethics, this literature review contributes to the ongoing discourse regarding assisting individuals in dealing with the moral challenges faced in modern contexts.